THE DEVELOPMENT OF DISCOVERY LEARNING - BASED E-BOOK TEACHING E-BOOK BASED ON KVISOFT FLIPBOOK MAKER ON SCIENCE LITERATION - Aswirna, Prima; Ritonga, A (State Institute of Islamic Studies (IAIN) Palu, 2020)
This research is motivated by the outstanding printed books that do not display interactive simulations by combining text, images, audio, video, and animation so that they are less attractive, the availability of communicative science learning media and have many interesting displays that have not yet been developed, teaching materials used in schools in the form of printed-based teaching materials such as physics textbooks and the availability of instructional media less utilizing existing technology in the learning process and lack of reading skills, interest in reading and lack of understanding of scientific concepts of students as well as the lazy nature possessed by students. Research and teaching materials e -Book discovery based flipbook maker kvisoft aided learning is a research and development ( Research and Developmet) by adapting the procedural step, namely ADDIE Analysis (analysis), Design (design), Development (development), Implementation (implementation) and Evaluation (evaluation). The validity test of e- book teaching materials based on discovery learning assisted by Kvisoft Flipbook Maker was conducted by five experts, two material experts, two media experts and one linguist. Practicality test of discovery learning based e- book teaching material assisted by flipbook maker kvisoft by looking at the practicality questionnaire sheet by science educators and some students of class X-MIA MAN 2 Padang Pariaman. Test the effectiveness of discovery learning based e-book teaching materials using Kvisoft Flipbook Maker by looking at the scientific literacy of students using the effectiveness questionnaire sheets by class X-MIA MAN 2 students in Padang Pariaman. The results showed, e- book teaching materials based on discovery learning assisted by Kvisoft Flipbook Maker on material momentum and impulses and simple harmonious vibrations of class X-MIA MAN 2 Padang Pariaman on the ability of students' scientific literacy, learning materials based on Kvisoft discovery learning assisted by Kvisoft flipbook maker on the material of momentum and impulses and simple harmonic vibrations class X-MIA MAN 2 Padang Pariaman is very valid with an average of getting 88.7% for the material of momentum, impulses and simple harmonic vibrations with a very valid category. Practicality results obtained an average value of 88.49% categorized as very practical, while for the effectiveness of e- book learning materials based on Discovery Learning assisted by Flipbook Maker obtained an average value of 80.89% for the scientific literacy ability of students. The results can be concluded that the e-book teaching material based on discovery learning assisted by Koftoft Flipbook maker on material momentum, impulses, and simple harmonic vibrations is very valid, very practical, and effectively used in physics learning class X MIPA -1 MAN 2 Padang Pariaman.